Fatigue crack retrofitting by closing crack surface. (February 2019) - YuanZhou, Zhiyuan; Ji, Bohai; Fu, Zhongqiu; Kainuma, Shigenobu; Tsukamoto, Shigeaki
Graphical abstract: Highlights: The crack will remain closed until the external stress becomes large enough. The stress intensity factor is found to reduce after closing the crack surface. An equivalent model describing the crack geometry is proposed. The stress intensity factor is measured based on the K-gage. Abstract: This paper mainly focuses on the mechanism of fatigue crack retrofitting by closing crack surface, which has proved to be effective in numerous experiments. The process of crack-closure treatment was simulated by using finite-element approach, and its effect on the crack propagation behavior was discussed in detail. It is found that the crack surface after impact treatment will remain closed until the external stress becomes large enough, however, when it opens, it will propagate again according to the analysis of crack-tip opening displacement. The stress intensity factor is found to reduce after closing the crack surface, resulting in the retardation of crack propagation. An internal-eccentric crack model is proposed as an equivalent model to describe the crack profile after closing the crack surface. Numerical and experimental investigations both support the findings of the simulations. As a result, fatigue crack propagation can be delayed due to the crack surface closure effect, which is the intended purpose of the fatigue crack retrofitting process.